The legal status of the Institute of inheritance in civil law (Journal of actual problems of jurisprudence, 2018)
The article considers issues of history of the origin, development and establishment of inheritance law as one of the most important institutes of civil law of the Republic of Kazakhstan. The authors show the role of the law of succession, as in the epoch of occurrence and currently. Considers the issues of formation of inheritance, originating in the common law of the Kazakhs up to the present time.Key words: inheritance, inheritance law, heir, terms of inheritance, inheritance.